The Effect of Gamification Implementation on Collaboration Skills, Engagement, and Learning Achievement of Students in Class X SMA XYZ - Lindawati Mustikasari; Pujianto Yugopuspito (Eduvest - Journal of Universal Studies, 2024)
This study explores the impact of gamification on students' collaboration skills, engagement, and learning achievement in the context of 21st-century education. Utilizing an experimental method, the research was conducted to observe the effects of implementing gamification, particularly through the Quizizz application, in classroom learning. The findings revealed that students in the experimental group, who experienced gamified learning, showed significant improvement in collaboration skills, engagement, and academic achievement compared to the control group. The application of gamification provided an interactive and engaging learning environment that promoted active participation and collaboration among students. The use of gamification as a learning strategy not only enhances students' soft skills but also contributes positively to their overall academic performance. These results suggest that gamification is an effective tool in modern educational settings, providing valuable insights for educators and policymakers to enhance learning outcomes.